Prevalence of asymptomatic bacteriuria - Faraj, Abdulmohaimen (faculty of applied basic medical science - Libyan international medical university, 2022)
Asymptomatic bacteriuria (ASB) is the presence of bacteria in a urine specimen received from a patient who does not have symptoms of a urinary tract infection,24 specimens collected from LIMU student's males and females to investigate the relationship between the gender and the prevalence rate of ASB. The collection performed by midstream catch urine specimen method, diagnosis based on colony-forming units (CFUs) per ml of urine. The result of using a FISHER test on SPSS program shows the P value equal 0.018 which is mean there is prevalence rate of ASB and the females
Keywords: Bacteriuria